Ответ:
Пошаговое объяснение:
1) x - 3y + x² - 9y² = (x - 3y) + (x² - 9y²) = (x - 3y) + (x - 3y) (x+3y) = (x - 3y)( 1 + x + 3y); 2) 9m² + 6mn + n² - 25= ( 9m² + 6mn + n²) - 25 = (3m + n)² - 25 = (3m + n - 5)(3m + n + 5); 3) ab⁵ - b⁵ - ab³ + b³ = ( ab⁵ - b⁵) - (ab³ - b³) = b⁵(a - 1) - b³(a - 1) = (a - 1)(b⁵ - b³) = b³(a - 1)(b² - 1) = b³(a - 1)(b - 1)(b + 1); 4) 1 - x² + 10xy - 25y² = 1 - (x² - 10xy + 25y²) = 1 - (x - 5y)² = (1 - x + 5y)(1 + x - 5y)
5,6-3(2-0,4х)=0,4(4х+1)
5,6-6+1,2х=1,6х+0,4
1,2х-1,6х=0,4+0,4
-0,4х=0,8
х=0,8:(-0,4)
х=-2
Х^2=36-20=16
Х=4
Проверка:
4^2=36-20
Ответ:
Пошаговое объяснен Угол АС+угол СВ= угол АВСие: